Baduanjin Exercise for Adults Aged 65 Years and Older: A Systematic Review and Meta-Analysis of Randomized Controlled Studies. (April 2022) - Jones, Cindy; Qi, Meiling; Xie, Zihui; Moyle, Wendy; Weeks, Benjamin; Li, Ping
This study performed a systematic review and meta-analysis to evaluate the health effects of Baduanjin exercise on adults aged 65 years and older. Chinese and English databases were electronically searched using search terms related to the PICO model from inception through June 2021. The study quality assessment and meta-analysis were conducted using the PEDro scale and RevMan 5.4 software. Eleven included Chinese studies, published between 2015 and 2021, recruited participants from the mainland of China. The aggregated results showed significant benefits of Baduanjin on physical function, walking ability, balance, and anxiety. A long-term Baduanjin intervention could also improve quality of life and reduce falls and pain. Baduanjin appears to have the potential to improve the health of older adults, but conclusions are limited due to the lack of rigorous and robust studies within and outside of mainland China. Larger, well-designed RCTs are needed to confirm these findings.